Determining the optimal threonine:lysine ratio in starter diets for the segregated early-weaned pig - J R Bergstrom; K Q Owen; B T Richert; W B Nessmith Jr; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1995)
A 35-day growth trial was conducted to determine the threonine: lysine ratio necessary to optimize growth performance of the segregated early-weaned (SEW) pig. Twelve experimental diets included two levels of lysine (1.15% and 1.5% digestible lysine) and six digestible threonine:lysine ratios (50, 55, 60, 65, 70, and 75%) in a 2 x 6 factorial arrangement. Growth performance was improved by feeding 1.5% digestible lysine, rather than 1. 15% digestible lysine. However, growth performance was not improved by increasing dietary threonine. These data indicate that the threonine requirement is no more than 50% of digestible lysine.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Early-weaned pigs; Amino acids; Threonine